2020
DOI: 10.1007/s42452-020-2616-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase and dimensional stability of volcanic ash-based phosphate inorganic polymers at elevated temperatures

Abstract: Phosphate geopolymers are part of chemically bonded phosphate cements obtained from an aluminosilicate and phosphate solution. Their structure consisting of phosphate bonds makes them suitable for use as refractory material. This study deals with the influence of phosphoric acid concentration (6, 8 and 10 mol/L) on the stability of volcanic ash-based phosphate geopolymers exposed to 100, 600 and 1000 °C. The results reveal that the onset of crystallization is about 600 °C with the formation of aluminum phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Volcanic ash and phosphate geopolymer show a single mass loss which is accompanied by an endothermic peak with maximum appearing before 100°C. That corresponds to the removal of different types of water [4]. In the phosphate cement, a very weak exothermic peak at around 650°C is identified which might be attributed to the transformation of amorphous iron phosphate phases from the binder into ferrous/ferric phosphate minerals [4].…”
Section: Mineralogymentioning
confidence: 95%
See 2 more Smart Citations
“…Volcanic ash and phosphate geopolymer show a single mass loss which is accompanied by an endothermic peak with maximum appearing before 100°C. That corresponds to the removal of different types of water [4]. In the phosphate cement, a very weak exothermic peak at around 650°C is identified which might be attributed to the transformation of amorphous iron phosphate phases from the binder into ferrous/ferric phosphate minerals [4].…”
Section: Mineralogymentioning
confidence: 95%
“…In literature, it was reported that the retardation effect of boric acid in the hydration of magnesium phosphate cement depends upon the dosage in the mix. With a lower dosage, it mainly acts on hindering the precipitation reaction (delay of the initial setting time) by stabilizing Mg 2+ ions with the formation of the complex MgB(OH) 4 + which makes the Mg 2+ ions less available to react with phosphate species [20], while for a higher dosage, it rather delays the dissolution reaction (delay of the final setting time) [22]. In this work, the initial and final setting times were delayed with the presence of boric acid.…”
Section: Setting Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the wavenumber is ascribed to an increase in the degree of condensation–polycondensation of the dissolved species, which leads to a longer polymeric chain with stronger bonds Si–O–P–O–Al/Al–O–P–. 14,22 The shift of the wavenumber of the main band is more pronounce (21 cm −1 ) for the series of MKMAP obtained with MAP solution having molar ratio Al/P = 1/3 than the other series obtained with MAP having molar ratio Al/P = 1.4/3 (11 cm −1 ). The latter corroborates well with the previous results presented in this work which show that MAP solutions with molar ratio Al/P = 1/3 are more reactive than MAP with molar ratio Al/P = 1.4/3.…”
Section: Resultsmentioning
confidence: 99%
“…9 The binder is amorphous and/or semi-crystalline depending on the synthesis conditions, and has been described as a solid solution of two or more of the following phases: aluminophosphate, silicoaluminophosphate, silicophosphate, iron phosphate, calcium phosphate, and magnesium phosphate. 6,[9][10][11][12][13][14] In recent work, the authors demonstrated that calcium phosphate and magnesium phosphate phase are responsible for the fast hardening at room temperature of the phosphate geopolymer. 9 Whereas aluminum and iron phosphate phases were found responsible for the high strength development mainly at a late age.…”
Section: Introductionmentioning
confidence: 99%